The Role of [18F]FDG PET/CT Prior to and During Neoadjuvant Chemotherapy for Soft Tissue Sarcomas - Stijn J.C. van der Burg; Bernies van der Hiel; Lotte Heimans; J. Martijn Kerst; Michel W.J.M. Wouters; Petur Snaebjornsson; Yvonne M. Schrage; Winette T.A. van der Graaf; Winan J. van Houdt (Current Oncology)
This retrospective, single-center study investigates the association between PET parameters and pathological response or disease recurrence in patients with soft tissue sarcoma (STS) treated with neoadjuvant chemotherapy (NACT). The maximum standardized uptake value (SUVmaxBL), metabolic tumor volume (MTVBL), and total lesion glycolysis (TLGBL) were measured at baseline [18F]FDG PET/CT and the change in percentage (ΔSUVmax, ΔMTV, ΔTLG) from baseline to early evaluation [18F]FDG PET/CT was calculated. The optimal cutoff values of the different PET parameters for pathological response, defined as <10% residual viable tumor (RVT) or >15% fibrosis/hyalinization, and recurrence-free survival were obtained for analysis. Forty-two patients who underwent baseline [18F]FDG PET/CT and NACT followed by surgery were included between January 2015 and January 2023. The primary diagnoses were angiosarcoma (n = 15), leiomyosarcoma (n = 15), sarcoma not otherwise specified (n = 9) and synovial sarcoma (n = 3). Twenty-eight (66.6%) patients underwent an early evaluation PET/CT. MTVBL, TLGBL, and ΔSUVmax (p = 0.024; p = 0.042, p = 0.009, respectively) values above the cutoff were associated with a pathological response based on RVT. ΔSUVmax, ΔMTV, and ΔTLG (p = 0.002; p = 0.019; p = 0.039, respectively) values above the cutoff were positively related to >15% fibrosis/hyalinization. MTVBL, TLGBL, and ΔMTV (p = 0.014; p = 0.022; p = 0.034, respectively) values above the cutoff were prognostic for the recurrence of disease. [18F]FDG PET/CT has a promising role in STS patients treated with NACT.